1988
DOI: 10.1017/s0016672300024307
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of rDNA containing type 1 insertion sequence in the distal nucleolus organiser ofDrosophila melanogaster: implications for the evolution of X and Y rDNA arrays

Abstract: SummaryThe ribosomal RNAs produced by the multigene families on the X and Y chromosomes of Drosophila melanogaster are very similar despite the apparent evolutionary isolation of the X and Y chromosomal rDNA. X–Y exchange through the rDNA is one mechanism that may promote co-evolution of the two gene clusters by transferring Y rDNA copies to the X chromosome. This hypothesis predicts that the proximal rDNA of X chromosomes will be Y-like. Consequently, rDNA variants found only on the X chromosome (such as thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…INS" genes decreased nearly equally in bbP5 and bbT6 (about 50%), INS II genes decreased slightly and also equally in the two bobbed mutants, while INS I genes decreased preferentially in bbP5. These results suggest the occurrence of differential clustering of these genes in the rDNA of the mutants as has already been demonstrated for INS II genes in the nucleolus organizer of the Y chromosome by Wellauer et al (1978), for INS I genes by Appels & Hilliker (1982), Sharp et al (1983) and England et al (1988) and for the three classes of genes by Terracol & Prud'homme (1986).…”
Section: Discussionsupporting
confidence: 76%
“…INS" genes decreased nearly equally in bbP5 and bbT6 (about 50%), INS II genes decreased slightly and also equally in the two bobbed mutants, while INS I genes decreased preferentially in bbP5. These results suggest the occurrence of differential clustering of these genes in the rDNA of the mutants as has already been demonstrated for INS II genes in the nucleolus organizer of the Y chromosome by Wellauer et al (1978), for INS I genes by Appels & Hilliker (1982), Sharp et al (1983) and England et al (1988) and for the three classes of genes by Terracol & Prud'homme (1986).…”
Section: Discussionsupporting
confidence: 76%
“…Similarity between X-and Y-linked rDNA arrays may be the result of exchange events, even if those events occur very rarely (Ohta & Dover 1983). England et al (1988) demonstrated that X-Y exchange events influence the structure of variation along the rDNA array when they showed that proximal rDNA repeats of the X chromosome are the most Y-like, and that the type I inserts, which are found only on the X chromosome, are clustered toward the centromere. The survey of Williams et al (1987) identified greater geographic diversity in Y-linked rDNA than in Xlinked rDNA, which they interpreted as evidence for selective constraints operating only on the X-linked array.…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms of this elimination could be unequal recombination. The same unit types are clustered in the rDNA locus (Appels & Hilliker, 1982;Sharp et a!., 1983;Salzano & Malva, 1984;Terracol & Prud'homme, 1986;Gillings et a!., 1987;Terracol, 1987;England et al, 1988) and can be eliminated together during such an event. The observation is inverted for the 15-16.2 kb fragments, which are more represented on the 1C line X chromosome: they had been either eliminated from the 3B line X chromosome or amplified in the 1C line X chromosome.…”
Section: Molecularresultsmentioning
confidence: 99%